Insulin Resistance and NAFLD: A Dangerous Liaison beyond the Genetics - Melania Manco (MDPI AG, 2017)
Over the last decade, the understanding of the association between insulin resistance (IR) and non-alcoholic fatty liver disease (NAFLD) has dramatically evolved. There is clear understanding that carriers of some common genetic variants, i.e., the patatin-like phospholipase domain-containing 3 (PNPLA3) or the transmembrane 6 superfamily member 2 (TM6SF2) are at risk of developing severe forms of NAFLD even in the presence of reduced or absent IR. In contrast, there are obese patients with "metabolic" (non-genetically driven) NAFLD who present severe IR. Owing to the epidemic obesity and the high prevalence of these genetic variants in the general population, the number of pediatric cases with combination of genetic and metabolic NAFLD is expected to be very high. Gut dysbiosis, excessive dietary intake of saturated fats/fructose-enriched foods and exposure to some chemicals contribute all to both IR and NAFLD, adding further complexity to the understanding of their relationship. Once NAFLD is established, IR can accelerate the progression to the more severe form of liver derangement that is the non-alcoholic steatohepatitis.